1999
DOI: 10.1111/j.1438-8677.1999.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance Measurements of Glossy Petals of Ranunculus lingua (Ranunculaceae) and of Non‐Glossy Petals of Heliopsis helianthoides (Asteraceae)

Abstract: A spectrophotometric comparison of the reflectance of glossy petals of Ranunculus lingua (Ranunculaceae) and nonglossy petals of Heliopsis helianthoides (Asteraceae) was made in relation to the angle of incidence of the incoming light. Additionally, the reflectance of petals of R. flammula, R. acris and R. repens (Ranunculaceae) was measured for comparative purposes. In the examined Ranunculus species, gloss is present around mirror geometry over the whole spectral range measured, including the UV region where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 26 publications
0
35
0
5
Order By: Relevance
“…When directionally illuminated, buttercup flowers display a strong gloss in addition to an overall matte-yellow colour ( figures 1 and 2). The glossy petals of Ranunculus have fascinated scientists for more than a century [5,22,23,38]. Pioneering work by Parkin [36,37] showed that the starch cells are arranged in a slanted manner and occur in many Ranunculus species.…”
Section: The Coloration Toolkit: a Pigmented Thin Film And Underlyingmentioning
confidence: 99%
See 2 more Smart Citations
“…When directionally illuminated, buttercup flowers display a strong gloss in addition to an overall matte-yellow colour ( figures 1 and 2). The glossy petals of Ranunculus have fascinated scientists for more than a century [5,22,23,38]. Pioneering work by Parkin [36,37] showed that the starch cells are arranged in a slanted manner and occur in many Ranunculus species.…”
Section: The Coloration Toolkit: a Pigmented Thin Film And Underlyingmentioning
confidence: 99%
“…are a clear exception to this rule, as they feature a distinct gloss (i.e. a mirror-like reflection) in addition to their overall yellow coloration [19,22,23]. Previous studies suggested that the gloss is due to the very flat and smooth epidermal layer that acts as a mirror [19,22], possibly enhanced by an air layer immediately below the epidermis [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the values for photoreceptor excitation are not angle-dependent [14], all measurements were taken in an angle of 45° to the measuring spot with a pellet of barium sulphate used as white standard and a black film can used as black standard. Reflectance measurements were taken in the same direction towards flower petals than transverse sections.…”
Section: Methodsmentioning
confidence: 99%
“…[13] we measured the spectral reflectance of two of the species surveyed ( O. pinnatum and D. sinuata ). As described above, petals were attached with double-sided tape to a glass slide.…”
Section: Methodsmentioning
confidence: 99%